STANDARD ENTHALPY OF FORMATION OF RUTHERFORDINE UO2CO 3(CR) - Devina O.A.; Sergeeva E.I.; Khodakovsky I.L. (My University, 2003)
As a continuation of a series of earlier publications devoted to the experimental determination of the thermodynamic properties of compounds in the system UO3-H2O-CO2, this paper presents the standard formation enthalpy of rutherfordine. The thermodynamic constants of crystalline uranyl carbonate UO 2CO3 (rutherfordine) are of interest as key values needed to determine the thermodynamic properties of the uranyl ion and its carbonate complexes in aqueous solutions. The enthalpy of dissolution of synthetic rutherfordine UO2CO3 in sodium carbonate aqueous solutions was determined calorimetrically at 298.15 K. The standard enthalpy of formation derived from experimental data is ΔfH298.15K0 UO2CO3(cr) = (-1697.2 ± 3.2) kJ mol -1. This value is consistent with the value of the standard formation enthalpy for rutherfordine calculated from a thermodynamic cycle including reliable data on rutherfordine and schoepite solubility. This procedure allowed us to exclude the possible uncertainty in the CODATA data on the entropy and free energy of formation for the UO22+ ion in an aqueous solution. The value of ΔfH298.15K0 UO2CO3(cr) =-1695.1 ± 1.5 kJ mol-1 thus obtained was selected, as a more reliable one, for further calculations.